Symptoms of Imperial Paranoia: Colonial Policing, Imprisonment, and Exile from a Southeast Asian Perspective - Kankan Xie (The Foundation for Law and International Affairs Review, 2022)
A panel discussion on "Empire and Regional Order", in which I discussed two related issues: 1. how to do research on the history of regional politics? 2. how to make sense of the unwritten by following what Ann Laura Stoler called “archival grains”.